2011
DOI: 10.4082/kjfm.2011.32.7.383
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of HbA1c as a Diagnostic Criterion of Diabetes

Abstract: BackgroundHemoglobin A1c (HbA1c) was adopted as a new standard criterion for diagnosing diabetes. We investigated the diagnostic utility of HbA1c by comparing the 2003 American Diabetes Association (ADA) diagnostic criteria of diabetes with HbA1c of 6.5%. Furthermore, the cut-off value for HbA1c was investigated using receiver operating characteristic curves.MethodsThis study included 224 subjects without a history of diabetes that had a fasting plasma glucose level of above 100 mg/dL. The subjects had undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…Several studies have computed different HbA 1c cut-off values for diagnosing diabetes mellitus based on OGTT ranging from ≥5.6 per cent (38 mmol/mol) to ≥7.0 per cent (53 mmol/mol)14151617181920. Several factors such as age, ethnicity, genetic makeup, erythrocyte lifespan and erythrocyte environment, which can influence glycosylation of haemoglobin2122232425, are likely to have contributed to these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have computed different HbA 1c cut-off values for diagnosing diabetes mellitus based on OGTT ranging from ≥5.6 per cent (38 mmol/mol) to ≥7.0 per cent (53 mmol/mol)14151617181920. Several factors such as age, ethnicity, genetic makeup, erythrocyte lifespan and erythrocyte environment, which can influence glycosylation of haemoglobin2122232425, are likely to have contributed to these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that about 25% of the population has IR and that the prevalence of IR is more than 80% in patients with T2DM (11)(12)(13). Guidelines for primary prevention of T2DM should identify categories of increased risk for DM (pre-DM), but many do not include the cut-off values of IR (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Even though some reports propose that HbA1c is useful as a diagnostic criterion of diabetes [7,8,11,39] others suggest that its diagnostic usefulness is inferior to standard testing because of a low sensitivity (26,(40)(41)(42). Our study showed that only 28.6% of the patients with levels of A1C ≥ 6.5% had 2-hPG >11.1 mmol/L.…”
Section: Resultsmentioning
confidence: 40%